Extracellular vesicles as surrogates for the regulation of the drug transporters ABCC2 (MRP2) and ABCG2 (BCRP) - Rigalli, Juan Pablo; Gagliardi, Anna; Diester, Klara; Bajraktari-Sylejmani, Gzona; Blank, Antje; Burhenne, Jürgen; Lenard, Alexander; Werntz, Lars; Huppertz, Andrea; Münch, Lena; Wendt, Janica Margrit; Sauter, Max; et al. (International journal of molecular sciences, 2024)
Drug efflux transporters of the ATP-binding-cassette superfamily play a major role in the availability and concentration of drugs at their site of action. ABCC2 (MRP2) and ABCG2 (BCRP) are among the most important drug transporters that determine the pharmacokinetics of many drugs and whose overexpression is associated with cancer chemoresistance. ABCC2 and ABCG2 expression is frequently altered during treatment, thus influencing efficacy and toxicity. Currently, there are no routine approaches available to closely monitor transporter expression. Here, we developed and validated a UPLC-MS/MS method to quantify ABCC2 and ABCG2 in extracellular vesicles (EVs) from cell culture and plasma. In this way, an association between ABCC2 protein levels and transporter activity in HepG2 cells treated with rifampicin and hypericin and their derived EVs was observed. Although ABCG2 was detected in MCF7 cell-derived EVs, the transporter levels in the vesicles did not reflect the expression in the cells. An analysis of plasma EVs from healthy volunteers confirmed, for the first time at the protein level, the presence of both transporters in more than half of the samples. Our findings support the potential of analyzing ABC transporters, and especially ABCC2, in EVs to estimate the transporter expression in HepG2 cells.